In-Patient Treatment of Fibromyalgia: A Controlled Nonrandomized Comparison of Conventional Medicine versus Integrative Medicine including Fasting Therapy. (23rd December 2012) - Michalsen, Andreas; Li, Chenying; Kaiser, Katharina; Lüdtke, Rainer; Meier, Larissa; Stange, Rainer; Kessler, Christian
Abstract : Fibromyalgia poses a challenge for therapy. Recent guidelines suggest that fibromyalgia should be treated within a multidisciplinary therapy approach. No data are available that evaluated multimodal treatment strategies of Integrative Medicine (IM). We conducted a controlled, nonrandomized pilot study that compared two inpatient treatment strategies, an IM approach that included fasting therapy and a conventional rheumatology (CM) approach. IM used fasting cure and Mind-Body-Medicine as specific methods. Of 48 included consecutive patients, 28 were treated with IM, 20 with CM. Primary outcome was change in the Fibromyalgia Impact Questionnaire (FIQ) score after the 2-week hospital stay. Secondary outcomes included scores of pain, depression, anxiety, and well being. Assessments were repeated after 12 weeks. At 2 weeks, there were significant improvements in the FIQ (P < 0.014 ) and for most of secondary outcomes for the IM group compared to the CM group. The beneficial effects for the IM approach were reduced after 12 weeks and no longer statistically significant with the exception of anxiety. Findings indicate that a multimodal IM treatment with fasting therapy might be superior to CM in the short term and not inferior in the mid term. Longer-term studies are warranted to assess the clinical impact of integrative multimodal treatment in fibromyalgia.